VIOLATED MAXIM IN OZ: THE GREAT AND POWERFUL MOVIE - Suci Retno Utami; Masitowarni Siregar (State University of Medan, 2014)
ABSTRACT The objectives of this research were discovered the kinds of maxims and the dominant maxim; to explain the implication of the dominant maxim and to describe the context of situation in OZ: the Great and Powerful Movie. This research was done on OZ’s utterances because he is the only main character. There were 38 of violated maxims gathered as the data for this research. The descriptive qualitative design was used to analyze the data. The results of the analysis showed that all kinds of maxims were violated: 18 utterances violated maxim of quantity (48%), 2 utterances violated maxim of qualiy (6%), 12 utterances violated maxim of relation (13%), and 6 utterances violated maxim of manner (13). The maxim of quantity is the dominant kind of maxims that was violated by OZ. The implication of this violated maxim is the main character has worried about his life story and he try to covered his truthfull and tricky. The context of situation of this violated maxim is the main character who cannot hide his true story from his friends Keyword: pragmatics, movie, violated maxim